XML publishing with InDesign CS2+ - Hopkins, Dorothy (O'Reilly shortcut., 2007)
From Adobe InDesign CS2 to InDesign CS5, the ability to work with XML content has been built into every version of InDesign. What in the (real) world could you do with XML if you understood how it works in InDesign? Some of the useful applications are importing database content into InDesign to create catalog pages, exporting XML that will be useful for subsequent publishing processes, and building chunks of content that can be reused in multiple publications. In this Short Cut, we'll play with the contents of a college course catalog and see how we can use XML for course descriptions, ta.